Strategi Komunikasi Corporate Social Responsibility Pabrik Gula Tjoekir terhadap Pondok Pesantren di Desa Cukir Jombang - Lailatus Sa’diyah; Robi'ah Machtumah Malayati (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2024)
This study aims to describe and illustrate the communication strategy of Corporate Social Responsibility (CSR) implemented by Pabrik Gula Tjoekir towards Islamic boarding schools (Pondok Pesantren) in Cukir Village, Diwek, Jombang, East Java. The research method is a qualitative approach using primary data based on interviews, observations, and documentation, as well as secondary data from various sources such as journals, articles, and related literature. The research subjects consist of the Assistant Secretary General and the Assistant Human Resources of Pabrik Gula Tjoekir as the parties responsible for CSR activities, and the Islamic boarding schools in the surrounding area, namely Pondok Pesantren Tebuireng, Pondok Pesantren Madrasatul Qur’an, Pondok Pesantren Putri Walisongo Cukir, and Pondok Pesantren Darul Falah IV Cukir as the recipients of CSR. The results indicate that the communication strategy involves determining the communication targets, selecting the media, and crafting the message, with the decision-making process involving key stakeholders, namely village heads and boarding school caretakers. The CSR focuses more on social and educational aspects, and there are discrepancies in CSR implementation related to the understanding of the surrounding community about the CSR concept.